1991
DOI: 10.3109/02841869109092385
|View full text |Cite
|
Sign up to set email alerts
|

Radiotherapy for Postoperative Recurrent Uterine Cervical Carcinoma

Abstract: From January 1980 to December 1985, a total of 110 patients with postoperative recurrent uterine cervical carcinoma were treated with radiotherapy. The mean age was 53 years. Ten patients were excluded due to incomplete treatment. The population was grouped according to the classification by Ciatto et al. into patients with central recurrence (n = 48), with peripheral limited recurrence (n = 43), and with peripheral massive recurrence (n = 9). The midpelvic dose given to patients with central recurrence was 40… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
13
0

Year Published

1998
1998
2013
2013

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 18 publications
3
13
0
Order By: Relevance
“…[86][87][88]90,92 In Hille et al, 86 grade 3 late toxicity was observed in 8% of patients, including intestinal bleeding after 7 months and fistulae between the rectosigmoid colon and the vagina, removed subsequently by surgery. In Ito et al, 87 late complications of radiotherapy, including intestinal and urinary complications of grade 2 and grade 3, occurred in 32% of patients.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…[86][87][88]90,92 In Hille et al, 86 grade 3 late toxicity was observed in 8% of patients, including intestinal bleeding after 7 months and fistulae between the rectosigmoid colon and the vagina, removed subsequently by surgery. In Ito et al, 87 late complications of radiotherapy, including intestinal and urinary complications of grade 2 and grade 3, occurred in 32% of patients.…”
Section: Resultsmentioning
confidence: 99%
“…In Jain et al, 88 one patient suffered from morbidity in the sigmoid colon requiring surgical resection and in Lucraft 90 seven cases of complications were observed, including transient proctitis, intermittent haematuria and severe acute bowel reactions. In Tan et al, 92 major complications included fistulae, proctitis and cystitis (see Table 44). …”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations